居住水準向上と住環境保全を両立させる地域地区見直し方法に関する研究(1) - 高見沢 実; 和多 治; 小泉 秀樹; 清田 伯人; 町田 弘一; 杉浦 達彦 (住宅総合研究財団研究年報, 1992)
In recent years there has been increasing pressure to relax urban planning regulations. Land prices particularly in the Tokyo metropolitan area have increased dramatically, and as a result, particularly in connection with the ability to pay in detached-housing residential areas, in exclusive areas for type-1 residential use where regulations are strict there has been mounting pressure to relax them. If the regulations are simply relaxed in response to this pressure, not only the operation of space which was the original aim of standard prices would be obstructed, but it is also possible that the living environment which up to now was ensured would deteriorate. In this relation, focusing on suburban residential areas of large cities where restrictions on designated use zones, particularly for floor area ratios and building coverage ratios, have become relatively strict, and realizing the various demands that occur in this type of area, especially improvement in dwelling level and preservation of living environment, the aim of this research is to make a proposal from within our accumulation of documented studies on methods to lead future “transformations” in a desirable way. In the first section, this study conducts advanced research based on trends in research on suburban residential areas. In particular, the fact that until now where has been little research on the designated effects of use zones, and that therefore there has been almost no research done on the effects of regulation relaxation, indicates the importance of this study. In the second section, taking the trends surrounding type-1 exclusive district for residential use, we examine them by separating them into their organizational side and the side related to the macroeconomic situation concerning their designation. In addition, we make clear the notable case of regulation relaxation in this type of area in a suburban residential district in the Tokyo metropolitan area. The third and fourth sections are case studies done in the cities of Yokohama and Kawasaki respectively. Relaxation of floor area ratio regulations in the former and the both floor area ratio and building coverage ratio regulations in the latter was carried out, and we clarify positively what kind of results were achieved by the changes through a fact-finding survey and a questionnaire survey. Based on section one through four, the fifth section makes a concrete proposal for new ways for rezoning of use districts. 近代都市計画制緩和の圧力が強まっている。また，東京大都市圏を中心に地価が暴騰し，この結果として，特に一戸建住宅地に対する支払い能力との関係で，規制の厳しい第1種住居専用地域において規制緩和圧力が強まっている。こうした圧力に対して単に緩和を行なうだけでは，基準値が本来目的としていた空間の形成が妨げられるばかりか，今まで確保されてきた住環境をも悪化させることになりかねない。そこで本研究は，指定された用途地域の制限，中でも容積率・建蔽率が相対的に厳しくなりつつある大都市郊外住宅地に焦点を絞り，そうした地域に発生する各種の需要，とりわけ居住水準の向上と住環境の保全を実現しながら，今後の「変容」をより望ましい方向に導く方法を，実証的スタディーの積み重ねの中から提案することを目的としている。まず第1章では，郊外住宅地の研究動向を踏まえて本研究の位置づけを行なっている。特にここでは，用途地域の指定効果に関する研究がこれまで少なかったこと，したがって規制緩和の効果に関する研究がほとんどなされておらずしたがって本研究の意義が大きいことを示している。次の第2章では，第一種住居専用地域をめぐる動向として，第一種住居専用地域の制度的側面と第一種住居専用地域指定のマクロな実態に関する側面とに分けて考察している。さらに，こうした地域の規制緩和が，東京大都市圏郊外住宅地に顕著であることを明らかにしている。続く第3章は横浜市の，第4章は川崎市のケーススタディーである。前者は容積率の緩和を後者は建蔽率と容積率の緩和を行なったが，それらがどのような結果をもたらしたかについて実態調査とアンケート調査を通して実証的に明らかにしている。第5章は，第1章から第4章を踏まえて，新しい用途地域見直し方法の具体的提案を行なっている。